Investigating the relationship between goal orientation, self-efficacy, positive emotionality, and affective engagement among Chinese students - WenQi Zhao; Rui Ma (Acta Psychologica)
This study delved into the complex interplay between self-efficacy, achievement goals, positive emotions, and affective engagement among university students in China. To achieve this, a stratified random sampling technique was employed, resulting in a sample of 391 students from four geographically distinct universities across China. The data collection relied on self-reported questionnaires that measured academic self-efficacy, goal orientation (specifically focusing on mastery versus performance goals), positive emotions, and various aspects of affective engagement, including enjoyment, satisfaction, and interest in learning. Structural equation modeling (SEM) served as the primary statistical tool to analyze the hypothesized relationships between these variables. The analysis revealed a network of positive associations, indicating that students with higher levels of self-efficacy and positive emotionality reported experiencing greater affective engagement in their academic pursuits. Furthermore, a stronger mastery goal orientation was associated with increased enjoyment, satisfaction, and interest in learning. Self-efficacy and positive emotionality also indirectly influenced affective engagement through goal orientation, suggesting that students with higher self-belief and positive emotions were more likely to adopt mastery goals, leading to more positive learning experiences. This study highlights the importance of self-efficacy, positive emotionality, and goal orientation in shaping students' affective engagement. By fostering these factors, educators can create more positive and engaging learning environments for university students.